Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis

Tryptique lesbien - Marchessault, Jovette (Éditions de la Pleine lune, 1980)
Keywords: 1900-1999; 1980-1989; amériques; cours; fem1000; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*

La pensée straight - Wittig, Monique (Questions Féministes, 1980)
Analyse de l'idéologie hétérosexuelle entreprise d'un point de vue lesbien et centrée sur les constructions intellectuelles des sciences humaines. An analysis of heterosexual ideology from a lesbian point of view, focusing upon the intellectual constructs of the social sciences.
Keywords: 1900-1999; 1970-1979; approches et analyses; com5170; cours; cycles supérieurs; europe; fem1000; fem7000; france; har4600; incontournable; lesbianisme; lit3220; premier cycle; périodes historiques; ressource en ligne; régions géographiques; soc2014; sofia; théories féministes